Reclaiming William Morris : Englishness, sublimity, and the rhetoric of dissent - Weinroth, Michelle (McGill-Queen's University Press, 1996)
Philosophical reflections : towards a theory of propaganda -- Conservative propaganda and the legacy of William Morris -- Propaganda of the Third International and the emerging Marxist Morris -- Martyrdom and the communist intellectual -- The irrationality of rationalist discourse : a phenomenology of communist propaganda -- "England, Our England" : the sublime poetics of communist community -- "The Biting Edge of British Humour" : the sublime patriotism of cold war communists.